Expression of Long Noncoding RNA, HOTAIR, and MicroRNA-205 and Their Relation to Transforming Growth Factor β1 in Patients with Alopecia Areata - Mohamad, Noha; Khedr, Ahmed M.B.; Shaker, Olfat Gamil; Hassan, Mohammed (Skin appendage disorders, 2023)
Introduction: Alopecia areata (AA) is a common autoimmune condition that affects anagen hair follicles. The most commonly recognized theory is that it is a T-cell-mediated autoimmune disorder in a genetically susceptible individual. MicroRNAs (miRNAs) and long noncoding RNAs (lncRNAs) were thought to play a function in the pathogenesis. The expression of lncRNA HOTAIR and miRNA-205 and their relation to transforming growth factor β1 (TGF-β1) in AA were not studied. Aim: The aim of the studywas to evaluate the role of miRNA-205, lncRNA, HOTAIR, and TGF-β1 levels in AA pathogenesis, clinical course, and severity of AA. Methods: Two groups of subjects were included in this case-control study: 50 patients with AA and 50 healthy matched controls. miRNA-205 and lncRNA HOTAIR expression levels were assayed using quantitative RT-PCR, while serum levels of TGF-β1 were assayed using ELISA techniques. Results: The serum expression of lncRNA HOTAIR was significantly downregulated in AA patients with a p value < 0.001, while the serum expression of both miRNA-205 and TGF-β1 were significantly upregulated in patients. Discussion/Conclusion: This study highlights the potential role of high serum expression of miRNA-205 and TGF-β1 and the low serum expression of lncRNA HOTAIR in AA pathogenesis. This could be used as a therapeutic target to treat AA.